2016
DOI: 10.1016/j.bios.2015.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Label-free biomolecular detection at electrically displaced liquid interfaces using interfacial electrokinetic transduction (IET)

Abstract: Biosensors require a biorecognition element that specifically binds to a target analyte, and a signal transducer, which converts this targeted binding event into a measurable signal. While current biosensing methods are capable of sensitively detecting a variety of target analytes in a laboratory setting, there are inherent difficulties in developing low-cost portable biosensors for point-of-care diagnostics using traditional optical, mass, or electroanalytical-based signal transducers. It is therefore importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Traditional metrics to quantify antibiotic susceptibility based on the half maximal inhibitory concentration (IC50) or minimum inhibitory concentration (MIC) are end-point measurements, which are not suited towards detecting heterogeneity in responses within a fluctuating environment. Singlecell techniques, on the other hand, for electrophysiology-based phenotypic analysis within a droplet [32] or by using impedance [33], [34], [35], or electro-rotational analysis [36], [37], are capable of quantifying subpopulations, but they have not been applied towards studying microbial heterogeneity after antibiotic treatments. In prior work, we have demonstrated that C. difficile cell wall capacitance measurements can identify subtle alterations in S-layer glycoproteins, which can occur due to strain-based morphological differences [38] or due to cell wall reconstitution under probiotic interactions [39], and which are correlated to the colonization ability of C. difficile [40].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional metrics to quantify antibiotic susceptibility based on the half maximal inhibitory concentration (IC50) or minimum inhibitory concentration (MIC) are end-point measurements, which are not suited towards detecting heterogeneity in responses within a fluctuating environment. Singlecell techniques, on the other hand, for electrophysiology-based phenotypic analysis within a droplet [32] or by using impedance [33], [34], [35], or electro-rotational analysis [36], [37], are capable of quantifying subpopulations, but they have not been applied towards studying microbial heterogeneity after antibiotic treatments. In prior work, we have demonstrated that C. difficile cell wall capacitance measurements can identify subtle alterations in S-layer glycoproteins, which can occur due to strain-based morphological differences [38] or due to cell wall reconstitution under probiotic interactions [39], and which are correlated to the colonization ability of C. difficile [40].…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we demonstrated that biomolecular binding in solution without nanoparticles produces a local increase in electrical conductivity difference across the liquid interface. 24 This was demonstrated this by measuring the magnitude of the interfacial deflection for different analyte concentrations during binding.…”
Section: Human Igg-protein Amentioning
confidence: 99%
“…23 Exploiting this phenomena, we demonstrated that biomolecular binding influences the electrical conductivity at the liquid interface, and that binding can be dynamically detected by monitoring interfacial deflection at varying positions down the microchannel. 24 Biorecognition is transduced as a change in electrokinetically-induced interfacial deflection in a process we have described as interfacial electrokinetic transduction (IET). 24 This approach was used to detect model avidin:biotin biomolecular binding at avidin concentrations as low as 50 femtomolar (fM), enabling it to compete with methods like surface plasmon resonance (SPR) (3 nm to 1.5 fM) 25 and enzyme-linked immunosorbent assays (ELISAs) (100 fM and below) 26 , which are the current standard of clinical sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as demands increase, all constituents in the biosensors can be designed and manufactured in large quantities at a low cost to satisfy the needs of users. 1 In 1953, Clark et al 2 first published a paper containing the fundamental ideas of a "biosensor". Moreover, in 1967, Updike and Hicks 3 successfully reported a biosensor for glucose detection.…”
Section: Introductionmentioning
confidence: 99%